Dissipative gap solitons and vortices in moiré optical lattices - Wang Li; Yan Zhenya; Zhu Yi; Zeng Jianhua (National Science Open)
Considerable attention has been recently paid to elucidation the linear, nonlinear and quantum physics of moiré patterns because of the innate extraordinary physical properties and potential applications. Particularly, moiré superlattices consisted of two periodic structures with a twist angle offer a new platform for studying soliton theory and its practical applications in various physical systems including optics, while such studies were so far limited to reversible or conservative nonlinear systems. Herein, we provide insight into soliton physics in dissipative physical settings with moiré optical lattices, using numerical simulations and theoretical analysis. We reveal linear localization-delocalization transitions, and find that such nonlinear settings support plentiful localized gap modes representing as dissipative gap solitons and vortices in periodic and aperiodic moiré optical lattices, and identify numerically the stable regions of these localized modes. Our predicted dissipative localized modes provide insightful understanding of soliton physics in dissipative nonlinear systems since dissipation is everywhere.